6.160 Problems 15901 to 16000

Table 6.319: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

15901

\[ {}y^{\prime } = \frac {y+1}{t +1} \]

15902

\[ {}y^{\prime } = \frac {y+2}{2 t +1} \]

15903

\[ {}\frac {3}{t^{2}} = \left (\frac {1}{\sqrt {y}}+\sqrt {y}\right ) y^{\prime } \]

15904

\[ {}3 \sin \left (x \right )-4 \cos \left (y\right ) y^{\prime } = 0 \]

15905

\[ {}\cos \left (y\right ) y^{\prime } = 8 \sin \left (8 t \right ) \]

15906

\[ {}y^{\prime }+k y = 0 \]

15907

\[ {}\left (5 x^{5}-4 \cos \left (x\right )\right ) x^{\prime }+2 \cos \left (9 t \right )+2 \sin \left (7 t \right ) = 0 \]

15908

\[ {}\cosh \left (6 t \right )+5 \sinh \left (4 t \right )+20 \sinh \left (y\right ) y^{\prime } = 0 \]

15909

\[ {}y^{\prime } = {\mathrm e}^{2 y+10 t} \]

15910

\[ {}y^{\prime } = {\mathrm e}^{3 y+2 t} \]

15911

\[ {}\sin \left (t \right )^{2} = \cos \left (y\right )^{2} y^{\prime } \]

15912

\[ {}3 \sin \left (t \right )-\sin \left (3 t \right ) = \left (\cos \left (4 y\right )-4 \cos \left (y\right )\right ) y^{\prime } \]

15913

\[ {}x^{\prime } = \frac {\sec \left (t \right )^{2}}{\sec \left (x\right ) \tan \left (x\right )} \]

15914

\[ {}\left (2-\frac {5}{y^{2}}\right ) y^{\prime }+4 \cos \left (x \right )^{2} = 0 \]

15915

\[ {}y^{\prime } = \frac {t^{3}}{y \sqrt {\left (1-y^{2}\right ) \left (t^{4}+9\right )}} \]

15916

\[ {}\tan \left (y\right ) \sec \left (y\right )^{2} y^{\prime }+\cos \left (2 x \right )^{3} \sin \left (2 x \right ) = 0 \]

15917

\[ {}y^{\prime } = \frac {\left (1+2 \,{\mathrm e}^{y}\right ) {\mathrm e}^{-y}}{t \ln \left (t \right )} \]

15918

\[ {}\sin \left (x^{2}\right ) x = \frac {\cos \left (\sqrt {y}\right ) y^{\prime }}{\sqrt {y}} \]

15919

\[ {}\frac {x -2}{x^{2}-4 x +3} = \frac {\left (1-\frac {1}{y}\right )^{2} y^{\prime }}{y^{2}} \]

15920

\[ {}\frac {\cos \left (y\right ) y^{\prime }}{\left (1-\sin \left (y\right )\right )^{2}} = \sin \left (x \right )^{3} \cos \left (x \right ) \]

15921

\[ {}y^{\prime } = \frac {\left (5-2 \cos \left (x \right )\right )^{3} \sin \left (x \right ) \cos \left (y\right )^{4}}{\sin \left (y\right )} \]

15922

\[ {}\frac {\sqrt {\ln \left (x \right )}}{x} = \frac {{\mathrm e}^{\frac {3}{y}} y^{\prime }}{y} \]

15923

\[ {}y^{\prime } = \frac {5^{-t}}{y^{2}} \]

15924

\[ {}y^{\prime } = t^{2} y^{2}+y^{2}-t^{2}-1 \]

15925

\[ {}y^{\prime } = y^{2}-3 y+2 \]

15926

\[ {}4 \left (x -1\right )^{2} y^{\prime }-3 \left (3+y\right )^{2} = 0 \]

15927

\[ {}y^{\prime } = \sin \left (t -y\right )+\sin \left (y+t \right ) \]

15928

\[ {}y^{\prime } = y^{3}+1 \]

15929

\[ {}y^{\prime } = y^{3}-1 \]

15930

\[ {}y^{\prime } = y^{3}+y \]

15931

\[ {}y^{\prime } = y^{3}-y^{2} \]

15932

\[ {}y^{\prime } = y^{3}-y \]

15933

\[ {}y^{\prime } = y^{3}+y \]

15934

\[ {}y^{\prime } = x^{3} \]

15935

\[ {}y^{\prime } = \cos \left (t \right ) \]

15936

\[ {}1 = \cos \left (y\right ) y^{\prime } \]

15937

\[ {}\sin \left (y \right )^{2} = x^{\prime } \]

15938

\[ {}y^{\prime } = \frac {\sqrt {t}}{y} \]

15939

\[ {}y^{\prime } = \sqrt {\frac {y}{t}} \]

15940

\[ {}y^{\prime } = \frac {{\mathrm e}^{t}}{y+1} \]

15941

\[ {}y^{\prime } = {\mathrm e}^{t -y} \]

15942

\[ {}y^{\prime } = \frac {y}{\ln \left (y\right )} \]

15943

\[ {}y^{\prime } = t \sin \left (t^{2}\right ) \]

15944

\[ {}y^{\prime } = \frac {1}{x^{2}+1} \]

15945

\[ {}y^{\prime } = \frac {\sin \left (x \right )}{\cos \left (y\right )+1} \]

15946

\[ {}y^{\prime } = \frac {3+y}{1+3 x} \]

15947

\[ {}y^{\prime } = {\mathrm e}^{x -y} \]

15948

\[ {}y^{\prime } = {\mathrm e}^{2 x -y} \]

15949

\[ {}y^{\prime } = \frac {1+3 y}{x +3} \]

15950

\[ {}y^{\prime } = y \cos \left (t \right ) \]

15951

\[ {}y^{\prime } = y^{2} \cos \left (t \right ) \]

15952

\[ {}y^{\prime } = \sqrt {y}\, \cos \left (t \right ) \]

15953

\[ {}y^{\prime }+f \left (t \right ) y = 0 \]

15954

\[ {}y^{\prime } = -\frac {y-2}{x -2} \]

15955

\[ {}y^{\prime } = \frac {x +y+3}{3 x +3 y+1} \]

15956

\[ {}y^{\prime } = \frac {x -y+2}{2 x -2 y-1} \]

15957

\[ {}y^{\prime } = \left (x +y-4\right )^{2} \]

15958

\[ {}y^{\prime } = \left (1+3 y\right )^{4} \]

15959

\[ {}y^{\prime } = 3 y \]

15960

\[ {}y^{\prime } = -y \]

15961

\[ {}y^{\prime } = y^{2}-y \]

15962

\[ {}y^{\prime } = 16 y-8 y^{2} \]

15963

\[ {}y^{\prime } = 12+4 y-y^{2} \]

15964

\[ {}y^{\prime } = f \left (t \right ) y \]

15965

\[ {}y^{\prime }-y = 10 \]

15966

\[ {}y^{\prime }-y = 2 \,{\mathrm e}^{-t} \]

15967

\[ {}y^{\prime }-y = 2 \cos \left (t \right ) \]

15968

\[ {}y^{\prime }-y = t^{2}-2 t \]

15969

\[ {}y^{\prime }-y = 4 t \,{\mathrm e}^{-t} \]

15970

\[ {}t y^{\prime }+y = t^{2} \]

15971

\[ {}t y^{\prime }+y = t \]

15972

\[ {}x y^{\prime }+y = x \,{\mathrm e}^{x} \]

15973

\[ {}x y^{\prime }+y = {\mathrm e}^{-x} \]

15974

\[ {}y^{\prime }-\frac {2 t y}{t^{2}+1} = 2 \]

15975

\[ {}y^{\prime }-\frac {4 t y}{4 t^{2}+1} = 4 t \]

15976

\[ {}y^{\prime } = 2 x +\frac {x y}{x^{2}-1} \]

15977

\[ {}y^{\prime }+y \cot \left (t \right ) = \cos \left (t \right ) \]

15978

\[ {}y^{\prime }-\frac {3 t y}{t^{2}-4} = t \]

15979

\[ {}y^{\prime }-\frac {4 t y}{4 t^{2}-9} = t \]

15980

\[ {}y^{\prime }-\frac {9 x y}{9 x^{2}+49} = x \]

15981

\[ {}y^{\prime }+2 y \cot \left (x \right ) = \cos \left (x \right ) \]

15982

\[ {}y^{\prime }+x y = x^{3} \]

15983

\[ {}y^{\prime }-x y = x \]

15984

\[ {}y^{\prime } = \frac {1}{y^{2}+x} \]

15985

\[ {}y^{\prime }-x = y \]

15986

\[ {}y-\left (x +3 y^{2}\right ) y^{\prime } = 0 \]

15987

\[ {}x^{\prime } = \frac {3 x t^{2}}{-t^{3}+1} \]

15988

\[ {}p^{\prime } = t^{3}+\frac {p}{t} \]

15989

\[ {}v^{\prime }+v = {\mathrm e}^{-s} \]

15990

\[ {}y^{\prime }-y = 4 \,{\mathrm e}^{t} \]

15991

\[ {}y^{\prime }+y = {\mathrm e}^{-t} \]

15992

\[ {}y^{\prime }+3 t^{2} y = {\mathrm e}^{-t^{3}} \]

15993

\[ {}y^{\prime }+2 t y = 2 t \]

15994

\[ {}t y^{\prime }+y = \cos \left (t \right ) \]

15995

\[ {}t y^{\prime }+y = 2 t \,{\mathrm e}^{t} \]

15996

\[ {}\left ({\mathrm e}^{t}+1\right ) y^{\prime }+{\mathrm e}^{t} y = t \]

15997

\[ {}\left (t^{2}+4\right ) y^{\prime }+2 t y = 2 t \]

15998

\[ {}x^{\prime } = x+t +1 \]

15999

\[ {}y^{\prime } = {\mathrm e}^{2 t}+2 y \]

16000

\[ {}y^{\prime }-\frac {y}{t} = \ln \left (t \right ) \]